DTNKonekuto an interest-driven peer-to-peer microblogging system over delay tolerant networks. - Sacedor, Paul Alvin V. (2017)
With the increasing popularity of websites like Twitter, microblogging has shown an astounding growth exhibiting human aspiration to share and consume information and knowledge. In recent years, it has been an empowering tool for news coverage and political movements. During this time, the efficacy of mobile devices such as smartphones has considerably increased, opening up better approaches to impart and share content. Unfortunately, not everyone is lucky enough to be able to obtain and enjoy the benefits of this technology. These are the people living in challenged areas particularly in geographical locations where there is no existing infrastructure. To address this issue, we design an interest-driven peer-to-peer microblogging system over delay tolerant networks using mobile devices as our primary communicating medium. Our approach leverages advancements in social network file sharing to facilitate better information dissemination and retrieval. Detailed simulation studies conducted demonstrate that the proposed scheme outperforms basic dissemination strategies in terms of the relevance of the retrieved information.
A special problem (B.S. Computer Science) -- University of the Philippines, Tacloban.